Ilaria, Ramelli. I romanzi antichi e il Cristianesimo: contesto e contatti. Madrid, Signifer, 2001, 300 pp - Lavalle, Raúl (2002)
Fil: Lavalle, Raúl. Pontificia Universidad Católica Argentina; Argentina